2014
DOI: 10.1021/ie5010515
|View full text |Cite
|
Sign up to set email alerts
|

CO2 Adsorption at Elevated Pressure and Temperature on Mg–Al Layered Double Hydroxide

Abstract: CO 2 adsorption at elevated pressure was studied in a Mg−Al (Mg/Al = 3) layered double hydroxide (LDH). The double-layered structure was prepared via a coprecipitation method. The sample's structure and microstructure evolutions were characterized using X-ray diffraction, scanning electron microscopy, N 2 adsorption, and thermogravimetric and calorimetric analyses. The CO 2 adsorption experiments were performed between 5 and 4350 kPa at different temperatures (30−350 °C). Elevated pressure experiments showed t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
14
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(16 citation statements)
references
References 41 publications
(75 reference statements)
2
14
0
Order By: Relevance
“…5(B)-(D)). These qualitatively illustrate that the chemical sorption of CO 2 is certain to occur during CO 2 capture, which has been also proved by some Literatures [1,2,14,15]. Consequently, it is concluded that the carbonation reaction of Mg(OH) 2 is certain to occur under the investigated capture conditions.…”
Section: Analysis Of Produced Carbonates During Co 2 Capturesupporting
confidence: 80%
See 2 more Smart Citations
“…5(B)-(D)). These qualitatively illustrate that the chemical sorption of CO 2 is certain to occur during CO 2 capture, which has been also proved by some Literatures [1,2,14,15]. Consequently, it is concluded that the carbonation reaction of Mg(OH) 2 is certain to occur under the investigated capture conditions.…”
Section: Analysis Of Produced Carbonates During Co 2 Capturesupporting
confidence: 80%
“…A variety of solid sorbents for CO 2 capture have been studied and reported in Literatures. According to the CO 2 adsorption mechanisms, these solid sorbents can be classified into two types: physisorbents (microporous and mesoporous inorganic and organic materials such as zeolites [3], silica gel [4], activated carbon [5], and metal-organic frameworks (MOFs) [6]) and chemisorbents (Ca-based materials such as CaO [7], alkali metal-based materials such as NaOH [8], K 2 CO 3 [9] and Na 2 CO 3 [10], and Mg-based materials such as Mg(OH) 2 [1,2], MgO [11][12][13], hydrotalcite [14,15], and alkali metal-promoted hydrotalcite [16][17][18][19]). Usually, these physisorbents and chemisorbents for CO 2 capture are separately used in the pressure/temperature swing adsorption (PSA/TSA) system at relatively low temperatures (even near ambient temperature) and the TSA system at different temperatures [20].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Research Progress and Trends of LDH Adsorption on CO 2 Although LHD has many advantages in the adsorption of CO 2 , there were still a lot of problems to be overcome in practical applications. In order to improve the adsorption capacity of LDH, the scholars have studied the conditions of synthesis, modification and compounding.…”
Section: Advances In Engineering Research Volume 129mentioning
confidence: 99%
“…Among various carbon dioxide capture and storage (CCS) technical options for CO 2 separation and capture, adsorption of CO 2 on solid adsorbents have been widely investigated. In recent years, layered double hydroxides (LDH) are the most promising candidates for the above applications, due to the characteristics of eco-friendly, cheap, easy to regenerate, wide range of process technology [2]. Especially, LDH as intermediate-temperature (200 ~ 400 ºC) CO 2 adsorbents have been extensively studied due to their optimal adsorption reaction temperature in the industrial flue gas temperature range.…”
mentioning
confidence: 99%